The Adolescent Resilience Questionnaire: Validation of a Shortened Version in U.S. Youths - Anderson, Jacqueline R.; Killian, Michael; Hughes, Jennifer L.; Rush, A. John; Trivedi, Madhukar H. (Frontiers in Psychology, 2020)
Introduction: Resilience is a factor in how youth respond to adversity. The 88-item Adolescent Resilience Questionnaire is a comprehensive, multi-dimensional self-report measure of resilience developed with Australian youth. Method: Using a cross-sectional adolescent population (n = 3222), confirmatory factor analysis was conducted to replicate the original factor structure. Over half of the adolescents were non-white and 9th graders with a mean age of 15.5. Results: Our exploratory factor analysis shortened the measure for which we conducted the psychometric analyses. The original factor structure was not replicated. The exploratory factor analysis provided a 49-item measure. Internal consistency reliability for all 12 factors ranged from acceptable (⍺ > .70 - .80). The revised factor total scores were highly and significantly correlated with item–total correlation coefficients (r > .63, p < .001). Conclusion: This revised shorter 49-item version of the Adolescent Resilience Questionnaire could be deployed and has acceptable psychometric properties.